Development of a prognostic model for survival time prediction in castration-resistant prostate cancer patients - Stangl-Kremser, Judith; Mari, Andrea; Suarez-Ibarrola, Rodrigo; D'Andrea, David; Korn, Stephan M; Pones, Mario; Kramer, Gero; Karakiewicz, Pierre; Enikeev, Dimitri V; Glybochko, Petri V; Briganti, Alberto; Shariat, Shahrokh F (Urologic oncology, 2020)
BACKGROUND: To identify predictors of survival in patients treated with docetaxel chemotherapy for castration-resistant prostate cancer (CRPC). METHODS: We retrospectively analyzed clinical data from 186 patients who underwent docetaxel chemotherapy for CRPC from 2005 to 2016 at a single center. Pretreatment baseline variables including demographic and clinicopathological data were reviewed. Disease progression was defined by imaging and/or consecutive prostate-specific antigen (PSA) elevation. The systemic immune-inflammation index (SII), the modified Glasgow Prognostic Score (mGPS), and the neutrophil-lymphocyte ratio (NLR) were calculated. Univariable and multivariable Cox proportional hazards regression analyses reporting hazard ratios assessed the risk for disease progression and overall survival (OS). A survival nomogram was constructed. RESULTS: Most patients (n = 139, 74.7%) completed at least 6 cycles of docetaxel chemotherapy. 156 patients (82.9%) experienced disease progression during the studied period. Only mGPS was independently associated with disease progression in a multivariable model (P < 0.01). During the studied period, 98 patients (52.1%) died. The built survival nomogram included statistically significant variables for OS in univariable analysis: hemoglobin, PSA, alkaline phosphatase (AP), lactate dehydrogenase, SII, neutrophil-lymphocyte ratio, mGPS, and site of metastases; and had a concordance index of 0.703. At decision curve analysis, the nomogram led to superior outcomes for any decision associated with a threshold probability of above 40%. In multivariable analysis, only AP (P = 0.02), hemoglobin and PSA (P < 0.01, respectively) remained associated with OS. CONCLUSIONS: PSA, AP, and hemoglobin are independent prognosticators for OS. Although mGPS is a promising marker for tumor progression and SII is a plausible prognostic marker for OS, valid integration of inflammatory indices into a prognostic model requires validation studies. Predictive and prognostic biomarkers are desperately needed to guide physicians in treatment counseling given the heterogeneous nature of CRPC and the plethora of effective therapies.
Keywords: senioři; Prognostic: Inflammation; statistické modely; Retrospective Studies; Prognosis; Time Factors; Prostatic Neoplasms, Castration-Resistant; Prostate cancer; Docetaxel; Middle Aged; mužské pohlaví; nádory prostaty rezistentní na kastraci; míra přežití; Antineoplastic Agents; docetaxel; prognóza; Models, Statistical; protinádorové látky; retrospektivní studie; Humans; Survival Rate; časové faktory; lidé středního věku; Aged; lidé; Male